Futility on the Border - Klugman, Craig M. (The Hastings Center report, 2013)
Miguel is an eighteen-year-old male transferred to Alamo Hospital for antivenom treatment after a rattlesnake bite while sleeping on railroad tracks. His “coyote,” an individual who guides undocumented people across the U.S. border from Mexico, dropped him off at a clinic. By the time Miguel was transferred from the clinic to Alamo, he was in complete paralysis and at risk for heart failure, requiring ventilator support to breathe. A person who receives treatment for a snake bite within one to two hours has a 99 percent chance of recovery, but for Miguel, at least fifteen hours had already passed. A hospital ethicist at Alamo contacted the Mexican consulate, and together they arranged for Miguel's father to come to Alamo and make decisions for him. His physicians have determined that he is in a persistent vegetative state and can no longer benefit from hospital treatment. However, no long-term care facility will accept him. Miguel is undocumented and unfunded. Miguel's father wishes to take his son home, but the cost of transporting him is high ,and their home state in Mexico has no ventilator available for him and no consistent supply of electricity to run it. What should the hospital do?